Analysis of the Implementation of the Independent Curriculum Project (P5) at SMK Negeri 1 Gelumbang - Wulan Prenika; Bangkit Seandi Taroreh (Universitas Muhammadiyah Enrekang, 2023)
The project of strengthening the profile of Pancasila students is one form of implementation of the current era of education. The purpose of this study is to describe the implementation of the project to strengthen the profile of Pancasila students on the theme of class X local wisdom at SMK Negeri 1 Gelumbang, Muara Enim Regency. In addition, obstacles occurred when the implementation of the project to strengthen the profile of Pancasila students on the theme of class X local wisdom at SMK Negeri 1 Gelumbang, Muara Enim Regency. And the solution carried out in overcoming the obstacles in the implementation of the project of strengthening the profile of Pancasila students on the theme (local wisdom) Class X at SMK Negeri 1 Gelumbang, Muara Enim Regency. This study uses classroom action research methods with qualitative descriptive models aimed at describing and describing existing phenomena, both natural and human engineering, which pay more attention to the characteristics, quality, relationships between activities. The sample in this study was all class X students with a total of 32. Based on the results of the study, it can be concluded that the analysis of the implementation of the Pancasila (P5) student profile strengthening project at SMK Negeri 1 Gelumbang, Muara Enim Regency runs in accordance with the project achievement target, namely students have high awareness of the importance of recognizing regional songs and dance movements for mental and physical health, students can also use it to grow creativity and critical reasoning